О температуре солидуса пород мантии - Гордиенко, В.В.; Гордиенко, И.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The accordance of the solidus temperature (Ts) of mantle rocks to a complex of petrological and geophysical data is considered. It is proved that the relation Ts = 1013 + 3.914H − 0.0037H2 , where H is the depth in km, corresponds to this information and can be used for the construction of models of the deep processes and the sources of anomalies of physical ﬁelds.